Peran Transparansi Keuangan Dalam Meningkatkan Kepercayaan Publik Pada Pemerintah Daerah - Rikza Pelaneta; Dinda Octaradani S; Nurul Aini; Sapira; Firni Febrianti; Abu Rizal Bakrie (Indo Publishing, 2026)
Financial transparency is one of the main principles in the implementation of good governance. In the context of local government, financial transparency plays an important role in creating accountability, improving the effectiveness of budget management, and strengthening public trust in the government. Public trust becomes a very important factor because it can influence the level of community participation in the regional development process and the success of implementing various public policies. This study aims to analyze the development of research on local government financial transparency and its relationship with public trust thru a bibliometric approach. Research data were obtained from scientific articles indexed in various academic databases and analyzed using the VOSviewer software. The analysis was conducted thru keyword co-occurrence mapping, overlay visualization, and density visualization. The research results show that transparency, accountability, governance, and public trust are closely related themes in the study of public sector accounting. In addition, recent research shows an increased focus on the use of digital technology to support financial transparency in local government. These findings indicate that financial transparency not only serves as an instrument of accountability but also as a means to build government legitimacy and enhance public trust in local government administration.